2021
DOI: 10.1007/s10291-021-01087-1
|View full text |Cite
|
Sign up to set email alerts
|

An open-source low-cost sensor for SNR-based GNSS reflectometry: design and long-term validation towards sea-level altimetry

Abstract: Monitoring sea level is critical due to climate change observed over the years. Global Navigation Satellite System Reflectometry (GNSS-R) has been widely demonstrated for coastal sea-level monitoring. The use of signal-to-noise ratio (SNR) observations from ground-based stations has been especially productive for altimetry applications. SNR records an interference pattern whose oscillation frequency allows retrieving the unknown reflector height. Here we report the development and validation of a complete hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…The first inter-comparison campaign on geodetic GNSS-R for sea level monitoring confirmed an RMSE smaller than 5 cm between GNSS-R-derived sea levels and tide gauge records at the Onsala GNSS-R tide gauge station [11]. The authors also demonstrated that the dominant tidal constituents were well captured by geodetic GNSS-R. More recently, [12] reported a 2.9 cm RMS for daily water levels at Guaiba Lake in Rio Grande do Sul by developing an open-source low-cost sensor for SNR-based GNSS reflectometry.…”
Section: Introductionmentioning
confidence: 75%
“…The first inter-comparison campaign on geodetic GNSS-R for sea level monitoring confirmed an RMSE smaller than 5 cm between GNSS-R-derived sea levels and tide gauge records at the Onsala GNSS-R tide gauge station [11]. The authors also demonstrated that the dominant tidal constituents were well captured by geodetic GNSS-R. More recently, [12] reported a 2.9 cm RMS for daily water levels at Guaiba Lake in Rio Grande do Sul by developing an open-source low-cost sensor for SNR-based GNSS reflectometry.…”
Section: Introductionmentioning
confidence: 75%
“…Gần đây, các thiết bị GNSS chi phí thấp hơn được sử dụng để theo dõi mực nước như ăng-ten GNSS tích hợp trên máy tính bảng sử dụng phương pháp phân tích quang phổ dựa trên biểu đồ Lomb -Scargle [28]. Các ăng-ten GNSS đa tần chi phí thấp được sử dụng bởi [29,30] đã cho thấy là phù hợp hơn so với các ăng-ten tiêu chuẩn trắc địa vì các ăng ten tiêu chuẩn trắc địa được thiết kế để giảm nhiễu đa đường (tín hiệu được sử dụng để truy xuất độ cao mực nước). Mặt khác, các ăng-ten GNSS đa tần sử dụng mô hình khuếch đại đẳng hướng nên có thể sử dụng các tín hiệu từ vệ tinh GNSS ở các góc cao vệ tinh lớn trong khi các ăng-ten tiêu chuẩn trắc địa chỉ sử dụng tín hiệu ở góc cao vệ tinh thấp để thực hiện phép đo mực nước [11,12].…”
Section: Mở đầU *unclassified
“…SNR-based GNSS-R has better response at low elevation satellites, where the multiple ray paths have similar polarization and direction of arrival [6]. Furthermore, as sensing occurs at slant incidence, sea surface altimetry is feasible from a sensor installed away from the water [7] Unfortunately, SNR-based GNSS-R needs approximately one hour per altimetry retrieval, as it relies on satellite elevation angle variations. The low retrieval rate is one of the main weakness of this technique [5].…”
Section: Introductionmentioning
confidence: 99%